2021
DOI: 10.1111/1365-2745.13756
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term effects of nutrient enrichment on salt marsh plant production and microbial community structure

Abstract: 1. Nutrient enrichment impacts ecosystems globally. Population history, especially past resource environments, of numerically dominant plant species may affect their responses to subsequent changes in nutrient availability. Eutrophication can also alter plant-microbe interactions via direct effects on associated microbial communities or indirect effects on dominant species' biomass production/allocation as a result of modified plant-soil interactions.2. We combined a greenhouse common garden and a field recipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 103 publications
(191 reference statements)
2
15
0
Order By: Relevance
“…Recent studies indicated the use of these marine resources by soil mesofauna of the salt marsh (Haynert et al, 2017 ; Winter et al, 2018 ). The activity of microbes breaking down plant material is influenced by abiotic factors such as soil temperature, water concentration, nutrient addition, and soil anoxia (Hanley et al, 2021 ; Hemminga & Buth, 1991 ). Therefore, changes in abiotic pressures across marsh zones may influence microbial processes via changes in microbial community composition and thereby their functioning as blue carbon system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated the use of these marine resources by soil mesofauna of the salt marsh (Haynert et al, 2017 ; Winter et al, 2018 ). The activity of microbes breaking down plant material is influenced by abiotic factors such as soil temperature, water concentration, nutrient addition, and soil anoxia (Hanley et al, 2021 ; Hemminga & Buth, 1991 ). Therefore, changes in abiotic pressures across marsh zones may influence microbial processes via changes in microbial community composition and thereby their functioning as blue carbon system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, changes in abiotic pressures across marsh zones may influence microbial processes via changes in microbial community composition and thereby their functioning as blue carbon system. However, most studies focusing on the breakdown of detrital material and microbial activity, investigated North American salt marshes (Gandy & Yoch, 1988 ; Hanley et al, 2021 ; Newell et al, 1989 ; Sherr & Payne, 1978 ), differing from Wadden Sea marshes in their microtidal range (<2 m) and their organogenic nature resulting in the accretion of organic material, rather than sediment (Allen, 2000 ; Kearney & Turner, 2016 ). Studies on European marshes focused on the rate of decomposition, the contribution of fungi or bacteria, and the fate of detrital material of salt marsh plants (Benner et al, 1984 ; Bouchard et al, 1998 ; Bouchard & Lefeuvre, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…3). Although exotic plants can invade low-resource ecosystems by optimizing their strategies (e.g., increasing root biomass allocation) to acquire and use resources 25,42 , the long-lasting effects of nutrient enrichment on plants (e.g., decreasing their nutrient acquisition e ciency) may compromise their ability to absorb nutrients [42][43][44] . Moreover, invasive plants can increase soil N by stimulating the decomposition of their nutrient-rich litter in fertile soils of terrestrial ecosystems 45,46 , but these oxic decomposition processes are largely limited in the water-saturated, anoxic sediments of wetlands 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated the use of these marine resources by soil mesofauna of the salt marsh . The activity of microbes breaking down plant material is influenced by abiotic factors such as soil temperature, water concentration, nutrient addition, and soil anoxia (Hanley et al, 2021;Hemminga & Buth, 1991). Therefore, changes in abiotic pressures across marsh zones may influence microbial processes via changes in microbial community composition and thereby their functioning as blue carbon system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, changes in abiotic pressures across marsh zones may influence microbial processes via changes in microbial community composition and thereby their functioning as blue carbon system. However, most studies focusing on the breakdown of detrital material and microbial activity, investigated North American salt marshes (Gandy & Yoch, 1988;Hanley et al, 2021;Newell et al, 1989;Sherr & Payne, 1978), differing from Wadden Sea marshes in their microtidal range (<2 m) and their organogenic nature resulting in the accretion of organic material, rather than sediment . Studies on European marshes focused on the rate of decomposition, the contribution of fungi or bacteria, and the fate of detrital material of salt marsh plants .…”
Section: Introductionmentioning
confidence: 99%